Aerospace series. Steel X5CrNiCu15-5 (1.4545). Consumable electrode remelted. Solution treated and precipitation treated. Plates. 6 mm < a ? 20 mm. 1 070 MPa ? Rm ? 1 220 MPa. (4th January 2023) - British Standards Institution,
No abstract available